A novel satellite layout optimization design method based on phi-function. (March 2021) - Chen, Xianqi; Yao, Wen; Zhao, Yong; Chen, Xiaoqian; Liu, Wei
Abstract: The purpose of this paper is to present a novel satellite layout optimization design (SLOD) approach based on the phi-function, which provides a simple, effective and simultaneously accurate way to handle the geometry constraints (including non-overlapping constraint and distance constraint) with an explicit mathematical expression. Firstly, an extended basic SLOD model concerning the system mass characteristics is formulated with the introduction of a generic minimum/maximum distance constraint between components. In the previous literature, most of the investigated SLOD applications only involve the planar circular and rectangular components with fixed orientation due to the lack of an effective and accurate overlap calculation method, let alone control the distance between them. Therefore, the idea of using phi-functions to prevent overlap and control distance between components is put forward to alleviate this difficulty. Furthermore, to effectively prevent the container protrusion from the components, the phi-function method is extended by our proposed finite-component-boundary (FCB) method. Despite its positive effects, the limitation of the phi-function is clearly discussed to provide a comprehensive view on this useful tool. Finally, the validity and the effectiveness of the proposed methodology are demonstrated by two numerical packing design examples, two typical 2D SLOD applications and one 3D cube-shaped SLOD application. Highlights: The satellite layout optimization design model with geometry constraints is built. Phi-function is used to handle the non-overlapping constraint between components. The finite-component-boundary method is proposed to prevent container protrusion. Phi-function extensions enable an easy distance control of different components. Limitation of phi-function in precisely representing overlap volume is illustrated.